2022
DOI: 10.1021/acs.inorgchem.2c00380
|View full text |Cite
|
Sign up to set email alerts
|

MOF-801 as a Nanoporous Water-Based Carrier System for In Situ Encapsulation and Sustained Release of 5-FU for Effective Cancer Therapy

Abstract: Nanoporous metal−organic frameworks (MOFs) have been gaining a reputation for their drug delivery applications. In the current work, MOF-801 was successfully prepared by a facile, cost-efficient, and environmentally friendly approach through the reaction of ZrCl 4 and fumaric acid as organic linkers to deliver 5-fluorouracil (5-FU). The prepared nanostructure was fully characterized by a series of analytical techniques including Fourier transform infrared spectroscopy, powder X-ray diffraction, field-emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 82 publications
(108 reference statements)
0
36
0
Order By: Relevance
“…Various approaches have been investigated with respect to enhancing the bioavailability and decreasing the toxicity of quercetin through encapsulation in drug delivery systems including silica nanoparticles, PLGA and PLA nanoparticles, , chitosan nanoparticles, metal and metal oxide nanoparticles, , phospholipid vesicles, , micelles, an inclusion complex, carbon nanotubes, and other nanomaterials. , Metal–organic frameworks (MOFs), which are known as a group of green and environmentally benign nanomaterials due to their unique advantages such as high storage capacity, an easy functionalizing process, resistance structure, and cytotoxicity, have been garnered much attention in recent years. Their wide range of possible metal clusters and organic linkers gives rise to a variety of properties, making them suitable for various applications such as catalysis, nanomaterial synthesis, gas storage, , antibacterial activity, and especially drug delivery. , However, the weak coordinate bond in MOFs leads to low stability, which makes them nonpractical for biomedical applications. Nevertheless, recent research indicated the excellent stability of the Zr-based MOF structure for drug delivery systems. , The synthesis of a high-capacity pressure-response drug release system of Zr-based MOF using novel ligand F–H 2 PDA ((2 E ,2′ E )-3,3′-(2-fluoro-1,4)­phenylene)­diacrylic acid) was reported by Qian et al The same research group fabricated another Zr-based MOF using N-heterocyclic ligand H 2 QDDA ((2 E ,2′ E )-3,3′-(quinolone-5,8-diyl)­diacrylic acid) with pH-response releasing properties . One of the most investigated Zr-based MOF drug-controlled release systems is UiO-66. A smart temperature-response drug release of UiO-66-PNIPAM (poly­( N -iso­propyl­acrylamide) was reported .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various approaches have been investigated with respect to enhancing the bioavailability and decreasing the toxicity of quercetin through encapsulation in drug delivery systems including silica nanoparticles, PLGA and PLA nanoparticles, , chitosan nanoparticles, metal and metal oxide nanoparticles, , phospholipid vesicles, , micelles, an inclusion complex, carbon nanotubes, and other nanomaterials. , Metal–organic frameworks (MOFs), which are known as a group of green and environmentally benign nanomaterials due to their unique advantages such as high storage capacity, an easy functionalizing process, resistance structure, and cytotoxicity, have been garnered much attention in recent years. Their wide range of possible metal clusters and organic linkers gives rise to a variety of properties, making them suitable for various applications such as catalysis, nanomaterial synthesis, gas storage, , antibacterial activity, and especially drug delivery. , However, the weak coordinate bond in MOFs leads to low stability, which makes them nonpractical for biomedical applications. Nevertheless, recent research indicated the excellent stability of the Zr-based MOF structure for drug delivery systems. , The synthesis of a high-capacity pressure-response drug release system of Zr-based MOF using novel ligand F–H 2 PDA ((2 E ,2′ E )-3,3′-(2-fluoro-1,4)­phenylene)­diacrylic acid) was reported by Qian et al The same research group fabricated another Zr-based MOF using N-heterocyclic ligand H 2 QDDA ((2 E ,2′ E )-3,3′-(quinolone-5,8-diyl)­diacrylic acid) with pH-response releasing properties . One of the most investigated Zr-based MOF drug-controlled release systems is UiO-66. A smart temperature-response drug release of UiO-66-PNIPAM (poly­( N -iso­propyl­acrylamide) was reported .…”
Section: Introductionmentioning
confidence: 99%
“…Their wide range of possible metal clusters and organic linkers gives rise to a variety of properties, making them suitable for various applications such as catalysis, 52 nanomaterial synthesis, 53 gas storage, 54,55 antibacterial activity, 56 and especially drug delivery. 57,58 However, the weak coordinate bond in MOFs leads to low stability, which makes them nonpractical for biomedical applications. 59−62 Nevertheless, recent research indicated the excellent stability of the Zr-based MOF structure for drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticle-based drug-delivery systems have become increasingly popular in recent years because of their numerous uncreditable advantages such as the ability to keep the drug from environmental effects, improve the stability of the drug, assist the transfer of drugs, reduce the toxicity, and need for one dose of the drug. , Therefore, various nanostructures have been applied in drug-delivery systems comprising dendrimers, polymersomes, micelles, liposomes, nanocapsules, hydrogels, and metal–organic frameworks (MOFs). MOFs are crystalline compounds formed from metal species and organic compounds through the self-assembling process. Recently, MOFs have been receiving increasing attention for their potential applications in gas adsorption, antibacterial activity, biocatalysis, , bioimaging , and biosensing. , MOFs are very valuable and practical porous nanostructures in drug-delivery systems because of their specific properties such as large surface areas, high pore volumes, and adjustable pore sizes. Recently, diverse MOFs such as MIL-100 (Fe), CD-MOF-1, , and UiO-66 (Zr) have been used for the delivery of antibiotics and antiinflammatory drugs . Zeolitic imidazole framework-8 (ZIF-8) and ZJU-802 were applied as carriers of doxorubicin and ibuprofen, respectively. , Among the numerous MOFs, Zr-based MOFs have been widely used as drug-delivery systems because of their high chemical stability (especially water stability), high level of biocompatibility, and high drug-loading capacity. Recently, a study showed that UiO-66 and its analogues with −NO 2 and −NH 2 functional groups were capable of the effective targeted delivery of QU .…”
Section: Introductionmentioning
confidence: 99%
“…MOFs, also known as porous coordination polymers, which can be constructed from metal ions or clusters and organic ligands through coordination bonds, , have shown wide applications in chemical sensing, energy storage, catalysis, drug delivery, separation, and bioimaging . Luminescent metal–organic frameworks combined the intrinsic photophysical property and porosity for the encapsulation of guest molecules, and the obtained guest@MOFs could act as platforms for host–guest interaction studies .…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, methods based on fluorescence "switch on" or enhancement are preferable to the "switch off" or quenching model because of the merits of higher sensitivity and better antiinterference of background signals. 24 MOFs, also known as porous coordination polymers, which can be constructed from metal ions or clusters and organic ligands through coordination bonds, 25,26 have shown wide applications in chemical sensing, 27−32 energy storage, 33 catalysis, 34 drug delivery, 35 separation, 36 and bioimaging. 37 Luminescent metal−organic frameworks combined the intrinsic photophysical property and porosity for the encapsulation of guest molecules, and the obtained guest@MOFs could act as platforms for host−guest interaction studies.…”
Section: Introductionmentioning
confidence: 99%